Single Cell Analysis of Drug Susceptibility of Mycobacterium abscessus during Macrophage Infection - Joanna Brzostek; Amierah Fatin; Wen Hui Chua; Hui Yi Tan; Thomas Dick; Nicholas R. J. Gascoigne (MDPI AG, 2020)
Mycobacterium abscessus is an emerging health risk to immunocompromised individuals and to people with pre-existing pulmonary conditions. As M. abscessus possesses multiple mechanisms of drug resistance, treatments of M. abscessus are of poor efficacy. Therefore, there is an urgent need for new therapeutic strategies targeting M. abscessus. We describe an experimental system for screening of compounds for their antimicrobial activity against intracellular M. abscessus using flow cytometry and imaging flow cytometry. The assay allows simultaneous analysis of multiple parameters, such as proportion of infected host cells, bacterial load per host cell from the infected population, and host cell viability. We verified the suitability of this method using two antibiotics with known activity against M. abscessus: clarithromycin and amikacin. Our analysis revealed a high degree of infection heterogeneity, which correlated with host cell size. A higher proportion of the larger host cells is infected with M. abscessus as compared to smaller host cells, and infected larger cells have higher intracellular bacterial burden than infected smaller cells. Clarithromycin treatment has a more pronounced effect on smaller host cells than on bigger host cells, suggesting that heterogeneity within the host cell population has an effect on antibiotic susceptibility of intracellular bacteria.